Encrypted email using 3D AES block cipher algorithm / Khairah Mohd Wi - Mohd Wi, Khairah (2015)
Encrypted email is addition mail that comes up with prototype application called,3D-AES block cipher. There are three objective designed: To identify an encrypted email application development of 3D AES block cipher algorithm and hash process, to develop encrypted email using 3D AES process on email and lastly to measure the validity of the encrypted & decrypted email message by comparing the hash value generate before encrypt and after decrypt. The purpose of this project is to develop encrypted email application equip with confidentiality and integrity message using 3D-AES block cipher for confidential and integrity. The main finding of this project will produces a security of message content. This new application will produces a higher security services: authentication, confidential and integrity. Lastly, this project had accomplish all their objective which important in process of developing the mail prototype application using3D-AES block cipher as confidential process as integrity purpose.